2010
DOI: 10.1111/j.1476-5381.2010.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Cis‐isomerism and other chemical requirements of steroidal agonists and partial agonists acting at TRPM3 channels

Abstract: BACKGROUND AND PURPOSE The transient receptor potential melastatin‐3 (TRPM3) channel forms calcium‐permeable, non‐selective, cationic channels that are stimulated by pregnenolone sulphate (PregS). Here, we aimed to define chemical requirements of this acute steroid action and potentially reveal novel stimulators with physiological relevance. EXPERIMENTAL APPROACH We used TRPM3 channels over‐expressed in HEK 293 cells, with intracellular calcium measurement and whole‐cell patch‐clamp recording techniques. KEY R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 29 publications
(48 reference statements)
8
71
0
Order By: Relevance
“…In contrast, in HEK293 cells engineered to express TRPM3 channels, gene transcription is activated following stimulation of TRPM3 stimulation with pregnenolone sulfate, independently of L-type voltage-gated Ca 21 channels (Lesch et al, 2014). Thus, TRPM3 functions in this heterologous system in the absence of L-type voltage-gated Ca 21 channels as a ligand-activated ionotropic receptor, leading to an influx of Ca 21 into the cells following activation (Wagner et al, 2008;Majeed et al, 2010). To elucidate the signaling pathway connecting TRPM3 stimulation with enhanced gene transcription of AP-1 responsive genes, we used this engineered HEK293 cell line, in which expression of TRPM3 is induced by adding tetracycline to the culture medium, as shown previously (Lesch et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in HEK293 cells engineered to express TRPM3 channels, gene transcription is activated following stimulation of TRPM3 stimulation with pregnenolone sulfate, independently of L-type voltage-gated Ca 21 channels (Lesch et al, 2014). Thus, TRPM3 functions in this heterologous system in the absence of L-type voltage-gated Ca 21 channels as a ligand-activated ionotropic receptor, leading to an influx of Ca 21 into the cells following activation (Wagner et al, 2008;Majeed et al, 2010). To elucidate the signaling pathway connecting TRPM3 stimulation with enhanced gene transcription of AP-1 responsive genes, we used this engineered HEK293 cell line, in which expression of TRPM3 is induced by adding tetracycline to the culture medium, as shown previously (Lesch et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…TRPM3 activation has frequently been monitored using either intracellular Ca 21 measurement with Ca 21 indicators and/or a whole-cell patch clamp to measure the cationic membrane current (Wagner et al, 2008;Majeed et al, 2010). Thus, the influx of Ca 21 ions into the cells and the subsequent rise in intracellular Ca 21 concentration was used as an indication for an activated TRPM3 channel.…”
Section: Introductionmentioning
confidence: 99%
“…Human TRPM2, TRPM3, and TRPC5 were expressed as described previously (McHugh et al, 2003;Zeng et al, 2004;Majeed et al, 2010). TRP channel cDNA, stably incorporated into human embryonic kidney 293 cells, was under the control of a tetracycline-inducible promoter such that addition of 1 g/ml tetracycline (Tetϩ) induced expression of channels.…”
Section: Methodsmentioning
confidence: 99%
“…The strongest known activator of TRPM3 channels is pregnenolone sulfate (Wagner et al, 2008;Majeed et al, 2010). However, the concentrations of pregnenolone sulfate required for activation are supraphysiological (Wagner et al, 2008;Naylor et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The neurosteroid pregnenolone sulphate rapidly activated TRPM3 channels in pancreatic β cells, indicative of direct neurosteroid binding to TRPM3 (Nilius and Voets, 2008, Wagner et al, 2008, Majeed et al, 2010, Majeed et al, 2012. It was also reported that stimulation of TRPC6 channels in cath.a differentiated (CAD) neuronal cells increased 2-AG release, which suggests that TRPC6 channels could activate endocannabinoid synthesis (Bardell and Barker, 2010).…”
Section: -Apb a Non-specific Trp Channel Blocker Markedly Reduced mentioning
confidence: 96%